Peningkatan Keterampilan Motorik Halus Melalui Latihan Kegiatan Menganyam dengan Bahan Alam pada Siswa TK B - Yrinne Naara Cheny Age; Christiana Hari Soetjiningsih; Enjang Wahyuningrum (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to enhance fine motor skills in grade B students at Hati Elok Kindergarten. The hypothesis proposed in this study is that there will be an improvement in the fine motor skills of grade B students at Hati Elok Kindergarten after they have been given training in weaving activities using natural materials. After participating in the weaving training, fine motor skills will be greater than before participating in the weaving activities. The research method employs quantitative research with a quasi-experimental one-group pretest-posttest design. The population of this study consists of students in class B at Hati Elok Kindergarten. The sampling technique used is saturated sampling, where all members of the population are included as samples. Data analysis in this study utilized the Wilcoxon Test. The results of the study indicate that weaving activities using natural materials are effective in improving fine motor skills in grade B students at Hati Elok Kindergarten, with a significance value (asymp. Sig. 2-tailed) of 0.0025. Since the value of 0.0025 is less than 0.005, the hypothesis in this study is accepted. The conclusion of this research is that weaving activities using natural materials are effective in enhancing the fine motor skills of grade B students at Hati Elok Kindergarten.